Kampanye Politik: Idealitas dan Tantangan - Robi Cahyadi Kurniawan (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2009)
Designing an ideal campaign is not simple. In the election process, campaign is the key point to accumulate votes. On the other hand, campaign also has role as the arena of political education. In such context, using the black campaign as one of existing campaign models in the process of political education could be backfiring. Henceforth media has the important role to approach and to encourage the more signijhnt campaign. By elaborating and comparing the face of political campaign and election campaign, this article describe the basic concept and the locus of the significant role of political campaign which seem rarely appear in the election process.